INCREMENTAL COST SEBAGAI SALAH SATU ALTERNATIF PADA PENGAMBILAN KEPUTUSAN JANGKA PENDEK - ADI ERAWATI, NI MADE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 1 (2010))
Relevant cost has been considered as an important factor in decision making based on the concept of different analysis for different purposes. One type of relevant cost is incremental cost, which is additional cost when an alternative is not chosen in a process of decision making. A decision can be classified as long and short range decision. Example of short range decision is special order, which is order from a buyer asking price below normal price, and often management directly refuses this order without further consideration. Concept of incremental cost can be used to evaluate this kind of problem. Some considerations in implementing the concept include cost identification, idle capacity, and variable costing system. Incremental cost analysis involves comparison among additional order, additional cost and contribution margin from the special order. This concept supported by variable costing method is important for companies implementing job order costing system before deciding to accept or refuse a special order.
Keywords: incremental cost, relevant cost, variable cost, job order